Relationship between Perceived Social Support and Risk of Postpartum Depression Disorder - Masoudnia E. PhD (Iran University of Medical Sciences, 2011)
Background & Aim: Postpartum depression (PPD) has negative effects on developmental and behavioral functions of newborn, mother-child relationship and mother's health. The etiology of postpartum depression is very complex. Social support is known as a risk factor for postpartum depression. Accordingly the aim of this study was to determine the relationship between social support and its components and incidence of postpartum depression.   Material & Methods: It was a cross-sectional study. The sample consisted of 140 mothers at least 5 weeks after their delivery. These mothers had been referred to Shahid Akbary and Shahid Motahhari hospitals in Yazd city to receive postpartum care. Data was collected by Perceived Social Support Scale (PSSS) and Beck Depression Inventory (BDI) and analyzed by SPSS-PC using principal components analysis, zero-rank Pearson correlation and hierarchical multiple regression.   Results: The results of the analysis suggest significant negative correlation between postpartum depression and total perceived social support (p < .001), family support (p < .001), significant others, support (p < .001), and friend support (p < .05). Hierarchical multiple regression analysis showed that the socio-demographic variables (Fetus age & sex) in the first model and social component in the second model explained %5.6, %12.6 of the variance of postpartum depression respectively.   Conclusion: Lack or insufficiency of social support in postpartum phase can be seen as a strong risk factor for postpartum depression. To prevent negative outcomes of postpartum depressions, encouragement of families, family networks, significant others and friends to support women in their antenatal and postpartum phase is recommended.